(untitled) (Revista Peruana de Investigación Educativa, 2017)
Based on a perspective of bilingualism as social practice and recent questioning of certain concepts attached to language learning from the field of applied linguistics, we analize the limitations posed by the distinction between first and second language (L1/L2) for addressing the complexity of bilingualisms in a teacher training program focused on intercultural bilingual education (IBE) at a university in Lima (Peru’s capital city). After a brief theoretical framework and a discussion of how linguistic and educational policies conceptualize the bilingual subject and the target of IBE, we present our analysis organized into two sections. In the first one, we address the contradictions between the way the institution represents the students in relation to their languages and the way they live their diverse bilingualisms. In the second section, we display three narratives from students in relation to their bilingual trajectories along their lives. In these two sections, we find important differences between the students’ experience and the identity and linguistic categories that the institutional discourse imposes on them; and we verify that categories such as L1 and L2 are no longer that useful in a changing reality characterized by cultural mobility and fluxes through communities and contexts.